Youth as Climate Change Messengers: A Picture Is Worth a Thousand Words. Issue 6 (December 2021) - Hendrickson Lohmeier, Jill; Thompson, Shanna Rose; Chen, Robert F.; Mishol, Stephen
Artwork created by children can effectively communicate science content, especially for topics that are of universal concern for the public but may cause apprehension, like climate change. This commentary describes artwork from a youth art contest about climate change in which the winning art was displayed on public buses. Young artists learned about climate science while creating images that adults and youth easily engaged with in public spaces. Thus, we suggest that connecting youth with science through art, and then using youth-generated art to engage the general public in science learning can be an effective vehicle for science communication.